Role of diagnostic laparoscopy in suspected abdominal tuberculosis - Gupta, Ashwani; Prasad, Nikhil; Shirale, Vaishali; Dubey, Neha; Dubey, Indu Bhushan (Asian Journal of Medical Sciences, 2022)
Background: The difficulty in confirming the diagnosis, morbidity and mortality associated with laparotomy in patients with abdominal Tuberculosis (TB) has generated interest in laparoscopy to obtain specimens for histological and microbiological assessment. Aims and Objectives: Difficulty in sample procurement, paucibacillary load and non-specific clinical, biochemical, and radiological features makes early diagnosis difficult in abdominal TB. Diagnostic laparoscopy with peritoneal biopsy can provide rapid and correct diagnosis of abdominal TB and reduce significant morbidity and mortality. Materials and Methods: Laparoscopy with umbilical port enabled direct inspection of peritoneum, intra-abdominal organs and facilitated obtaining biopsy specimens, cultures, and aspiration. Results: Diagnostic laparoscopy has an important role not only in diagnosing abdominal TB, but also to rule out TB in certain cases. In our study, mesenteric lymphadenopathy was present in 85% of cases, tubercles in 63% and adhesions in 73%. An alternative diagnosis was established in 6 suspected abdominal TB patients (20%) who were microbiologically confirmed TB negative. Conclusion: The study showed the feasibility of diagnostic laparoscopy in diagnosis of abdominal TB by sampling macroscopically visible pathological tissue with a low complication and conversion rate in most patients with suspected TB, and also providing an alternative diagnosis.